Recruitment of agrarian temporary workforce in the campaigns for the fruit harvesting - Allepuz Capdevila, Rafael; Torres Solé, Teresa (Cuadernos de Relaciones Laborales, 2018)
The article performs an analysis of how labor legislation has regulated the hiring of temporary workers in recent decades. The novelty of the work is its application to the fruit sector. The results obtained through the analysis of the legislation, its effects and in-depth interviews, show that the working conditions that offer collection campaigns lead to leaks of the seasonal workers to other sectors despite the progressive adaptation of legislation to the needs of fruit farms. It is observed that the different strategies of recruitment of temporary labor have led to a process of substitution between domestic and foreign laborers, very conditional on the economic situation of the time. With the turn of the century, contractual preferences displayed initially by fruit businesspeople, which relied on the collective management of procurement at origin, port the recruitment of workers through subcontracting and the provision of workers, as it would be the case of the TEA (Temporary Employment Agencies).
Keywords: agrarian temporary workforce; contracting; fruit farming; working conditions